Neural correlates of intimate picture stimuli in females. (30th March 2018) - Maier, Simon; Spiegelberg, Julia; Jacob, Gitta; van Zutphen, Linda; Zeeck, Almut; Hartmann, Armin; Tüscher, Oliver; Holovics, Lukas; van Elst, Ludger Tebartz; Joos, Andreas
Abstract: Jacob et al. (2011) previously reported on intimate picture stimuli for emotion research in females in Psychiatry Research. Difficulties to engage in intimate relations constitute problems of many mental disorders, and intimacy must be differentiated from pure sex drive. Functional neuroimaging is an important tool to understand the pathophysiology of psychiatric disorders. We now studied cerebral activation in response to intimate stimuli in 35 healthy women. Comparison stimuli were taken from the International Affective Picture System. Neuroimaging revealed increased activation in bilateral occipitotemporal, parietal and anterior cingulate cortices extending to the orbitofrontal area. These data reflect cognitive, emotional and motivational compounds congruent with previous neuroimaging data of attachment and long term romantic relationships. Lateral prefrontal, posterior insular regions and the fusiform face area were more active during control images. Our data present a solid basis for use in psychiatric samples. Highlights: This study examined neural correlates of visual intimate stimuli in 35 non-patients. There was increased cerebral activation in bilateral occipitotemporal, parietal and anterior cingulate/ orbitofrontal cortices. This paradigm and data can be used for comparisons with psychiatric samples.